Prime Time tweets: a thematic analysis of Deion Sanders's tweets and social media's role in shaping the construction and perceptions of sports figure authenticity - Singer, Mara F., author; Champ, Joseph, advisor; Donavan, D. Todd, committee member; Famulari, Umberto, committee member; Hoffman, K. Doug, committee member; Johnson, Emily, committee member (Colorado State University. Libraries, 2025)
This dissertation explores the intersection of social media, personal branding, and fan perceptions of authenticity in the context of modern sports figures, focusing on the case of Deion 'Coach Prime' Sanders. Through two related studies, this research aims to better understand how Sanders leverages social media to build his personal brand and cultivate authentic connections with audiences. The first study employs focus groups and thematic analysis to examine how social media users perceive and construct Sanders's authenticity through his X (formerly Twitter) content. The second study conducts a qualitative thematic analysis of Sanders's X posts during his inaugural season as head football coach at the University of Colorado to identify authenticity management strategies. Ultimately framed by Actor-Network Theory, this research utilizes frameworks of perceived authenticity and authenticity management to provide a comprehensive understanding of the creation and reception of authenticity in sports figures' social media content. The findings offer insights into the factors influencing perceptions of sports figure authenticity on social media and the strategies employed to manage authentic self-presentation. This research contributes to digital sports media, personal branding, and fan engagement by addressing gaps in the literature regarding coaches' social media use and offering practical implications for sports organizations and figures aiming to build authentic connections with online audiences.
Keywords: authenticity; fans perceptions; sports marketing; digital charisma; Actor Network Theory; personal branding